Commemorating Maulidur Rasul - UMP, PNC (2019)
Muslims need to learn and commemorate Maulidur Rasul and the struggle endured by Prophet Muhammad (peace be upon him) in upholding the Islamic law. The narration of the personality of Prophet Muhammad (pbuh) who always practised moderation must be embodied in daily life. The Deputy Vice-Chancellor (Student Affairs & Alumni), Professor Dato’ Dr. Yuserrie Zainuddin said that the sacrifice of Prophet Muhammad (pbuh) and his companions blessed us with Iman and Islam today.